Impact of the COVID-19 Pandemic on Older Adult Driving in the United States. (August 2022) - Betz, Marian E.; Fowler, Nicole R.; Han, S. Duke; Hill, Linda L.; Johnson, Rachel L.; Meador, Lauren; Omeragic, Faris; Peterson, Ryan A.; DiGuiseppi, Carolyn
Objectives: To examine how the COVID-19 pandemic affected driving and health outcomes in older adults. Methods: We compared Advancing Understanding of Transportation Options (AUTO) study participants enrolled before (December 2019 to March 2020) versus during the pandemic (May 2020 to June 2021). Participants were English-speaking, licensed drivers (≥70 years) who drove weekly and had a primary care provider at a study site and ≥1 medical condition potentially associated with driving cessation. We used baseline self-reported measures on mobility and health. Results: Compared to those enrolled pre-COVID-19 ( n = 61), more participants enrolled during COVID-19 ( n = 240) reported driving reductions (26% vs. 70%, p < . 001) and more often for personal preference (vs. medical/emotional reasons). While mean social isolation was higher during than pre-COVID-19, self-reported depression, stress, and overall health PROMIS scores did not differ significantly. Discussion: Our findings highlight the resiliency of some older adults and have implications for mitigating the negative effects of driving cessation.